Determination of drying characteristics and quality properties of eggplant in different drying conditions - Gözde Bayraktaroglu Urun; Ünal Rıza Yaman; Ergun Köse (Chiriotti Editori, 2015)
Drying is the most traditional process used for preserving eggplant a long time. The aim of this study was to determining drying characteristics and quality properties of eggplant dried by sun drying, hot air convective drying and infrared assisted convective drying. Convective drying and infrared assisted convective were carried out in a convective dryer at three different temperatures (40°, 50°, 60°C) and air velocity at 5 m/s. The increasing of temperatures during the drying of eggplant led to a significant reduction of the drying time. However loss of nutrition was observed in eggplant samples dried at higher temperature. The biggest change in colour parameters was observed in samples dried with sun drying. So it was thought that sun drying had a negative effect on quality properties of eggplant samples.